Thermal structure and sediment bulk density of the MV420 mud volcano on the continental slope of the Canadian Beaufort Sea and its implications for the plumbing system - Kim, Young-Gyun; Jin, Young Keun; Hong, Jong Kuk; Paull, Charles; Caress, David; Jang, ChanHee; So, Byung-Dal (Frontiers in Earth Science, 2022)
The shallow migration path of mudflow of the mud volcano MV420 on the continental slope of the Canadian Beaufort Sea is investigated in terms of thermal and geotechnical characteristics. MV420 is a nearly flat topped active mud volcano that emits methane and fluidized mud. Its top is at a depth of water of 420 m, within the gas hydrate stability zone. During the summer 2017 IBRV Araon expedition, several measurements of marine heat flow were conducted in the area of juvenile mud mound/pond morphologies identified by multibeam bathymetry and backscatter intensity images obtained by the Monterey Bay Aquarium Research Institute’s autonomous underwater vehicle. The heat probe (a gravity corer with temperature, pressure, and tilt sensors) appeared to penetrate to a depth of >70 m below the seafloor. The sediment bulk density in the mudflow migration path of MV420, estimated by pressure change with controlled stretches of a winch cable, was 1.56 g/cm3. The subsurface temperature reaches up to 18°C and profiles show that the maximum local temperature occurs from 20 to 40 m below the seafloor, implying substantial vertical variability of geothermal gradients. Our finding of large positive and small negative geothermal gradients above and below the depth of the local temperature maximum may represent stagnant hot mud along the mudflow migration path, indicating a pulsative eruption of the mudflow. Gas hydrate is stable only within a few meter thick layer near the seafloor above the path because of the cold bottom water (0.4°C) covering the top of the mud volcano. Furthermore, the thermal conductivity of 0.939 W/m/K and the marine heat flow of 22.5 mW/m2 at a control site outside MV420 is estimated as the background heat flow in the slope, for which little data exists.